Individualization of a representative daily trend of pollutant concentrations as characteristic scenario to be simulated by mathematical models - Tirabassi, Tiziano (Ciência e Natura, 2002)
The paper presents a daily trend of pollutant concentrations, referred to as the “representative day”, i.e. the day for which the overall sum of the mean-square differences between its concentration, averaged within each hour, and the concentrations for all other days at the same hour, is a minimum. The approach also allows the identification of the “least representative day” (the daily series that maximises the mean sum of squared residuals).The purpose of such typifying is that of outlining characteristic scenarios for a given period under investigation and than mathematical models make it possible to attempt simulations of a typical period trend, without the need to simulate all the days of the time interval covered by the typical period.